Clínica ampliada na infância : a compreensão de profissionais da estratégia de saúde da família - Romano, Diana Carla (Universidade Federal de São Carlos, 2016)
The crisis in care management is evident over the new challenges of modern epidemiology, which comprises the complex phenomenon that links the biological to the psychological, social and ecological factors. Hence, the "Clinica Ampliada"(CA) is committed to offer high standards on health care considering the subject as a whole. The childhood years were chosen due to the relevance of this phase to the development of society. The aim of this study is to acknowledge the "Estratégia de Saúde da Família" team members perception about "Clinica Ampliada" over childhood. This is a scoping, descriptive study with a qualitative approach. Participants are nurses, doctors, dentists, nurses assistants, community health workers and dental assistants of family health units. For data collection a semi-structured interview guide was utilized, and from the CA theoretical foundation, the analysis by thematic categories was conducted. From a total of 32 participants, 50 per cent of the professionals have between 25 and 35 years of age, mostly female and work at USF more than five years. It was found that 19 subjects have already heard about the CA term and professionals with higher education were the ones who described the concept with more facility and coherence. A gap was evidenced between what they noted as CA and what they do or can do in their day to day routine. Therefore, the subjects pointed out to elements that contribute to the implementation of CA in childhood, such as enlargement of the object's concept, health care model, support management and emotional support. The participants recognized the positive contribution that the ESF scenary provides for the expansion and clinic better quality, mainly for working with the principles of comprehensive care, teamwork, home care and intersectionality. It was concluded that the path for the CA consolidation in childhood is the strengthening of child role and EPS.
Keywords: Clínica ampliada; Infância; Desenvolvimento integral infantil; Atenção primária a saúde; Estratégia de saúde da família; Expanded clinic; Childhood; Child integral development; Primary health care; Family health strategy; CIENCIAS DA SAUDE